2021
DOI: 10.3389/fbioe.2021.731749
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Chinese Leek Extract Incorporated Cellulose Composite Films

Abstract: This study aimed to prepare microcrystalline cellulose (MCC) films with good mechanical properties via plasticization using a Chinese leek (CL, Allium tuberosum) extract. The microstructure, crystal structure, mechanical properties, barrier ability, and thermal properties of the films were investigated. The chemical structure analysis of CL extract showed the existence of cellulose, lignin, and low-molecular-weight substances, such as polysaccharides, pectins, and waxes, which could act as plasticizers to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In addition, extrusion, granulation, and compression methods have been proved to be highly effective, while photocuring and thermal curing are also essential techniques that should not be overlooked in film fabrication. 76,118,133,136,149,150 However, through testing in research, it has been found that these general membrane fabrication technologies still have certain limitations in terms of the optical and mechanical performance of lignin-containing biodegradable UV-blocking films. As a result, many researchers have started exploring advanced technologies to improve the performance of films.…”
Section: General Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, extrusion, granulation, and compression methods have been proved to be highly effective, while photocuring and thermal curing are also essential techniques that should not be overlooked in film fabrication. 76,118,133,136,149,150 However, through testing in research, it has been found that these general membrane fabrication technologies still have certain limitations in terms of the optical and mechanical performance of lignin-containing biodegradable UV-blocking films. As a result, many researchers have started exploring advanced technologies to improve the performance of films.…”
Section: General Technologiesmentioning
confidence: 99%
“…The inclusion of cellulose, lignin, and other components from CL markedly enhanced the mechanical properties and UV-shielding capabilities of the MCC films. 76 Another sustainable packaging contender arises from lignin-containing CWNF (cationic wood nanofiber) films, derived from sawdust through mechanical disassembly in water suspension. These films boast exceptional visible light transparency and mechanical strength, positioning them as environmentally friendly protection packaging materials.…”
Section: Biodegradable Substratesmentioning
confidence: 99%
See 1 more Smart Citation